Mental Health Help-Seeking and Associated Factors Among Public Health Workers During the COVID-19 Outbreak in China - She, Rui; Wang, Xiaohui; Zhang, Zhoubin; Li, Jinghua; Xu, Jingdong; You, Hua; Li, Yan; Liang, Yuan; Li, Shan; Ma, Lina; Wang, Xinran; Chen, Xiuyuan; et al. (Frontiers in Public Health, 2021)
Background: The COVID-19 outbreak in China has created multiple stressors that threaten individuals’ mental health, especially among public health workers (PHW) who are devoted to COVID-19 control and prevention work. This study aimed to investigate the prevalence of mental help-seeking and associated factors among PHW using Andersen’s Behavioral Model of Health Services Use (BMHSU). Methods: A cross-sectional survey was conducted among 9,475 PHW in five provinces across China between February 18 and March 1, 2020. The subsample data of those who reported probable mental health problems were analyzed for this report (n=3,417). Logistic and hierarchical regression analyses were conducted to examine the associations of predisposing, enabling, need, and COVID-19 contextual factors with mental health help-seeking. Results: Only 12.7% of PHW reported professional mental help-seeking during the COVID-19 outbreak. PHW who were older, had more days of overnight work, received psychological training, perceived a higher level of support from the society, had depression and anxiety were more likely to report mental help-seeking (ORm range: 1.02 1.73, all p<0.05) while those worked in Centers for Disease Control and Prevention were less likely to seek help (ORm=0.57, p<0.01). The belief that mental health issues were not the priority (64.4%), lack of time (56.4%), and shortage of psychologists (32.7%) were the most frequently endorsed reasons for not seeking help. Conclusions: The application of BMHSU confirmed associations between some factors and PHW’s mental health help-seeking. Effective interventions are warranted to promote mental health help-seeking of PHW to ameliorate the negative impact of mental illness and facilitate personal recovery and routine work.